1998
DOI: 10.1007/pl00009965
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-adrenergic non-cholinergic inhibitory nerves in the colon of patients with ulcerative colitis

Abstract: The cause of impaired colonic motility in patients with ulcerative colitis (UC) is unknown. The non-adrenergic non-cholinergic (NANC) inhibitory nervous system is one of the most important factors in the enteric nervous system of human gut. To assess the physiological significance of NANC inhibitory nerves in the colon of patients with UC, we investigated the enteric nerve responses of colonic tissues from patients with this disease. Colonic tissues were obtained from the lesional sigmoid colons of six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…The enhanced TTX-resistant contractions were reduced by SR140333, suggesting that, in DD, there is unmasking of the actions of TTX-resistant terminals that release tachykinin(s); alterations in cannabinoid mechanisms were also reported (Guagnini et al, 2006) ]NKA(4 -10) was also seen in UC, although the effect was not as great as that seen in DD. This decreased contractility to NKA and SP has been reported previously (Tomita et al, 2000;Menzies et al, 2001;Liu et al, 2002), and mechanisms have been explored. For example, in UC, there is evidence that interleukin-6 (Vrees et al, 2002) and hydrogen peroxide (Cao et al, 2004) contribute to the decrease of NKAinduced Ca 2ϩ release from intracellular Ca 2ϩ stores.…”
Section: Discussionsupporting
confidence: 52%
“…The enhanced TTX-resistant contractions were reduced by SR140333, suggesting that, in DD, there is unmasking of the actions of TTX-resistant terminals that release tachykinin(s); alterations in cannabinoid mechanisms were also reported (Guagnini et al, 2006) ]NKA(4 -10) was also seen in UC, although the effect was not as great as that seen in DD. This decreased contractility to NKA and SP has been reported previously (Tomita et al, 2000;Menzies et al, 2001;Liu et al, 2002), and mechanisms have been explored. For example, in UC, there is evidence that interleukin-6 (Vrees et al, 2002) and hydrogen peroxide (Cao et al, 2004) contribute to the decrease of NKAinduced Ca 2ϩ release from intracellular Ca 2ϩ stores.…”
Section: Discussionsupporting
confidence: 52%
“…Abnormal colonic motor function occurs in patients with ulcerative colitis (Koch et al, 1988;Tomita et al, 1998;Al-Saffar and Hellstrom, 2001) and in animal models of colitis (Sethi and Sarna, 1991;Lu et al, 1997;Tsukamoto et al, 1997;Hosseini et al, 1999;Shi and Sarna, 2000;Gonzalez and Sarna, 2001). We have shown that neurokinin A and EFS-induced contraction were reduced in ulcerative colitis.…”
Section: Spontaneous Contractions and Ulcerative Colitis 1353mentioning
confidence: 89%
“…It should be mentioned that all these observations are at variance with other functional and immunohistochemical studies. Indeed Tomita et al (1998) reported that the colon from patients with UC was more strongly innervated by NANC inhibitory nerves, with NO as major neurotransmitter, than was the normal colon and Belai et al (1997) observed increased VIP, NOS and PACAP immunoreactivity in the myenteric plexus and nerve ®bres of the circular muscle layer of the a icted segment of the ileum of patients with Crohn's disease. The reason for this discrepancy is unclear but it would be of interest to study the role of VIP-ergic neurotransmission in our model.…”
Section: Discussionmentioning
confidence: 99%